Estudos de casos e casos exemplares: Um aspecto da fundamentaç\~ao de propostas de políticas públicas - Valdir Melo (Instituto de Pesquisa Econômica Aplicada (IPEA), 2020)
– Surveys of cases and case studies enrich the fund of knowledge that may serve as a base for proposals of public policy. The present text gives two reasons and constructs a defense of case studies. First, natural sciences - or, perhaps should one say, mixed sciences - also investigate cases, so that the method of cases is not a peculiarity of the social sciences. Second, one may resort to two major methodological notions, that of model and that of Kuhn's exemplars. Hence, one may interpret a relevant case within a discipline as a scientific or cognitive model of actual or possible cases in the field. An alternative interpretation is to see some relevant cases as exemplars (paradigmatic cases).
Keywords: B40; 330; case studies; nomothetic and idiographic; scientific model; Kuhn's exemplars